2005
DOI: 10.1287/orsc.1040.0113
|View full text |Cite
|
Sign up to set email alerts
|

Should I Keep a Secret? The Effects of Trade Secret Protection Procedures on Employees' Obligations to Protect Trade Secrets

Abstract: Organizations' trade secrets (which can be chemical formulae, recipes, customer files, machinery designs, or many other types of information) are often valuable, enduring sources of competitive advantage. In this study, the influence of organizations' formal efforts to protect trade secrets on employees' beliefs about their obligations to protect those secrets was investigated. Quantitative and qualitative data were gathered by means of survey interviews with 111 employees of two high-tech organizations. Emplo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
133
1
4

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 136 publications
(141 citation statements)
references
References 25 publications
3
133
1
4
Order By: Relevance
“…Numerous studies have found that the protection of innovations and prevention of imitation is the main motive for patenting (Arundel et al, 1995, Blind et al, 2006, Cohen et al, 2000, Duguet and Kabla, 1998, Giuri et al, 2007, Granstrand, 1999, Thumm, 2004a, Veer and Jell, 2012, Thumm, 2004b. Publishing is not associated with such benefits, while secrecy is (Arundel, 2001, Hannah, 2005. This leads to the first proposition.…”
Section: Innovation Appropriation Strategiesmentioning
confidence: 99%
“…Numerous studies have found that the protection of innovations and prevention of imitation is the main motive for patenting (Arundel et al, 1995, Blind et al, 2006, Cohen et al, 2000, Duguet and Kabla, 1998, Giuri et al, 2007, Granstrand, 1999, Thumm, 2004a, Veer and Jell, 2012, Thumm, 2004b. Publishing is not associated with such benefits, while secrecy is (Arundel, 2001, Hannah, 2005. This leads to the first proposition.…”
Section: Innovation Appropriation Strategiesmentioning
confidence: 99%
“…For some firms, implementing due diligence within the rather unregulated European market is a strategic decision they are reluctant to take as a first mover. Accordingly, regulation presents a trust-building facilitator demanding concerted levels of supply chain transparency among all firms, curtailing concerns of competitive disadvantage (Doorey, 2011), and enabling exchange of confidential information (Hannah, 2005).…”
Section: Enablers and Barriers Of Implementing Supply Chain Due Diligmentioning
confidence: 99%
“…Managers can address these issues through continuous monitoring, and by evaluating, for example, the trustworthiness of employees already during the recruitment interviews (Olander and Hurmelinna-Laukkanen, 2015). In general, the HR practices that are targeted towards limiting unwanted knowledge flows, i.e., knowledge securing practices, can cover means such as non-disclosure agreements, confidentiality clauses, enforcing non-competition agreements (applicable only with certain employees), educating employees on confidentiality issues, motivational aspects for following information security rules, sanctions for breaking the rules, and controlling and restricting access, (Baughn et al, 1997;Bulgurcu et al, 2010;Hannah, 2005;Hannah and Robertson, 2016;Olander et al, 2015;O'Neill and Adya, 2007;Porter Liebeskind, 1996;.…”
Section: Hrm Practices -Connection To Knowledge Protection and Sharingmentioning
confidence: 99%